Practical Implementation of Failure Mode and Effects Analysis for Extracorporeal Membrane Oxygenation Activation. (September 2018) - Nasim, Faria; Poterucha, Joseph T.; Daniels, Lisa M.; Park, John G.; Seelhammer, Troy G.; Bohman, John K.; Friedrich, Tammy P.; Blau, Caitlin L.; Elmer, Jennifer L.; Schears, Gregory J.
Extracorporeal membrane oxygenation (ECMO) is used to treat severe hypoxemic respiratory failure and as a rescue therapy for patients with cardiopulmonary arrest within a narrow window of time. A failure modes and effects analysis (FMEA) was conducted to analyze the clinical and operational processes leading to delays in initiating ECMO. FMEA determined these highest-risk failure modes that were contributing to process failure: (1) ECMO candidacy not determined in time, (2) no or incomplete evaluation for ECMO prior to consult or arrest, (3) ECMO team not immediately available, and (4) cannulation not completed in time. When implemented collectively, a total of 4 interventions addressed more than 95% of the system failures. These interventions were (1) ECMO response pager held by a team required for decision, (2) distribution of institutionally defined inclusion/exclusion criteria, (3) educational training for clinicians consulting the ECMO team, and (4) establishment of a mobile ECMO insertion cart.